Impact of respiratory viruses in the neonatal intensive care unit. (November 2018) - Shui, Jessica; Messina, Maria; Hill-Ricciuti, Alexandra; Maykowski, Philip; Leone, Tina; Sahni, Rakesh; Isler, Joseph; Saiman, Lisa
Abstract Objective To describe the epidemiology and clinical impact of respiratory viruses in a neonatal intensive care unit (NICU). Study design We conducted a retrospective observational study of infants with respiratory viruses detected by multiplex reverse-transcriptase PCR from May 2012 to May 2017. The proportion of symptomatic vs. asymptomatic infants and associated morbidity were assessed. The association of infection prevention and control (IP&C) strategies and transmission was ascertained. Results Respiratory viruses were detected in 83 infants representing 86 unique episodes during which infants remained asymptomatic in 15 (17%). Of the 71 symptomatic episodes, only 45% were associated with increased respiratory and/or nutritional support. Rhinovirus/enteroviruses were most common (69%) and involved nine of 12 transmission events. IP&C strategies including restricting visitors <12 years of age and screening exposed infants were associated with decreased transmission rates. Conclusions NICU patients can be asymptomatic carriers of respiratory viruses. Identification of such infants is important to prevent transmission in the NICU.